HUBUNGAN LAMA DUDUK DAN LAMA BERDIRI DENGAN NYERI PUNGGUNG BAWAH MIOGENIK PADA PEKERJA PERUSAHAAN PERIKLANAN ONLINE DAN PERUSAHAAN INDUSTRI OTOMOTIF - Abiyyu Dwi Pangestu; nia kurniawati (Jurnal Fisioterapi dan Kesehatan Indonesia, 2022)
Background: If Muscle receives a static load continuously with wrong positionand prolonged can cause complaints the parts of the skeletal muscles. Myogeniclow back pain is pain in the lower back that is dull and does not radiate to the legs caused by disorders in the elementtendomuscular. NordicMusculoskeletalQuestionnaire (NMQ) is an instrument that isinternationally designed to standardize evaluating musculoskeletal complaints.Methode:Typeofresearchusedinthisstudyisdescriptivecorrelationbyanalyzing the object of research with cross sectional research design. Result: atprongedsittingwithNPBhasP=0.162andprolongedstandingP=0.230withp<α = 0.05, which means that both the prolonged sitting and standing is notsignifican. Conclusion: There was no significant relationship between duration ofsitting and standing time with low back pain in company of online advertingandotomotifIindustri workers.